(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The aim of this pilot study was to assess the reliability and validity of the questionnaire in young women ≥18 years as tool to examine knowledge, attitudes and behaviors towards screening and vaccination against HPV and reliable source of information. Methods: Reliability analysis was tested and content validity was evaluated using Cronbach’s alpha to check internal consistency with the intention to obtain no misunderstanding results. The questionnaire - composed by n. 3 section for a total of n. 69 items- was administered to 30 girls. The study was conducted in 4 Italian cities: Ferrara, Rome, Cassino and Palermo and data were collected in the month of October 2010. Statistical analysis was performed through SPSS 19.0, statistical software for Windows. Results: The higher value of Cronbach’s alpha resulted on 24 items (alpha= 0,774). The addition just one at time of also only one more of the others items got worse the alpha. Cronbach’s alpha on all the III section together (n. 69 items) resulted in a value of 0, 059. Young women generally known HPV can cause cervical cancer (93.3%) and genital warts (16.7%) and 76.7% of them recognize pap test as a screening tool. The main sources of information about HPV vaccination, are represented by magazines / books (33.3%), TV (26.7%), gynecologists (23.3%). Conclusion: This pilot study demonstrated that a reduced version of the questionnaire showed a very good reliability properties in the study and this needs to be taken into account for future studies.